Oculomotor Deficits and Symptom Severity Are Associated With Poorer Dynamic Mobility in Chronic Mild Traumatic Brain Injury - D'Silva, Linda J.; Chalise, Prabhakar; Obaidat, Sakher; Rippee, Michael; Devos, Hannes (Frontiers in Neurology, 2021)
Oculomotor deficits, vestibular impairments, and persistent symptoms are common after a mild traumatic brain injury (mTBI); however, the relationship between visual-vestibular deficits, symptom severity, and dynamic mobility tasks is unclear. Twenty-three individuals (mean age 55.7 ± 9.3 years) with persistent symptoms after mTBI, who were between 3 months to 2 years post-injury were compared with 23 age and sex-matched controls. Oculomotor deficits [depth perception, near-point convergence, baseline visual acuity (BLVA), perception time], vestibular deficits (dynamic visual acuity in the pitch and yaw planes), dynamic mobility measured by the Functional Gait Assessment (FGA), and symptoms measured by the Post-Concussion Symptom Scale (PCSS) and Dizziness Handicap Inventory (DHI) were compared between groups. Participants with mTBI had poorer performance on the FGA (p < 0.001), higher symptom severity on the PCSS (p < 0.001), and higher DHI scores (p < 0.001) compared to controls. Significant differences were seen on specific items of the FGA between individuals with mTBI and controls during walking with horizontal head turns (p = 0.002), walking with vertical head tilts (p < 0.001), walking with eyes closed (p = 0.003), and stair climbing (p = 0.001). FGA performance was correlated with weeks since concussion (r = −0.67, p < 0.001), depth perception (r = −0.5348, p < 0.001), near point convergence (r = −0.4717, p = 0.001), baseline visual acuity (r = −0.4435, p = 0.002); as well as with symptoms on the PCSS (r = −0.668, p < 0.001), and DHI (r = −0.811, p < 0.001). Dynamic balance deficits persist in chronic mTBI and may be addressed using multifaceted rehabilitation strategies to address oculomotor dysfunction, post-concussion symptoms, and perception of handicap due to dizziness.